A systematic review on informal waste picking: Occupational hazards and health outcomes. (1st May 2021) - Zolnikov, Tara Rava; Furio, Frances; Cruvinel, Vanessa; Richards, June
Highlights: Waste pickers experience a significant amount of adverse health effects. This study comprehensively reviewed 61 studies to identify the most common hazards. Major occupational risks were physical (78.7%), social (70.5%), biological (65.6%). Major health outcomes included epidermal (50.8%) and communicable disease (47.5%). These are the most common occupational risks and health outcomes in waste pickers. Abstract: Informal waste picking is a common way for people to earn an income, especially in low-income countries; unfortunately, there are various occupational hazards and health outcomes associated with waste picking. This study focused on comprehensively identifying and exploring occupational hazards and health outcomes associated with informal waste picking. A systematic review of available relevant and peer-reviewed literature was completed to exhaustively analyze the full scope of these hazards and outcomes associated with informal waste picking; 58 papers were included. The results from this study provided insight and information related to the most common occupational hazards and negative health outcomes associated with informal waste pickers outlined in available literature. The most common reported occupational hazards were physical (77.6%), social (70.7%), biological (65.5%), chemical and safety (53.4%), ergonomic (34.5%) and mechanic (25.9%). Health outcomes appeared to include epidermal (50.0%), communicable disease (46.6%), musculoskeletal (44.8%), respiratory disease (41.4%), non-communicable diseases (39.7%), physiological (34.5%), gastrointestinal (31.0%) and waterborne diseases (17.2%). Physical hazards were often associated with slips, trips, and falls, which makes sense because of the unstable environment where waste pickers work. Health outcomes related to these hazards included bruises, cuts, and lacerations. This information also aligns with health outcomes, as epidermal outcomes were most reported in waste pickers (50.0% of data). It is clear that moving forward, additional research related to these occupational hazards and health outcomes associated with informal waste picking is needed to help create change in this affected population, as well as finding effective solutions to mitigate these hazards and outcomes. These hazards can be mitigated by simple, common control measures, like providing safety equipment, reducing hazards from the outside environment (e.g., less time in sun, breaks, etc.), and placing barriers between waste pickers and the hazards (e.g., covered stations, flat ground, etc.) or more complex engineering, administrative or work controls. Because of the breadth of health problems faced by workers, more research is needed to correctly assess health outcomes (e.g. use of health practitioners) in waste pickers across time to ensure accurate data and a focused answer to the far-reaching problem.